The properties of new epoxy networks swollen with ionic liquids. Issue 61 (13th June 2016) - Leclère, M.; Livi, S.; Maréchal, M.; Picard, L.; Duchet-Rumeau, J.
Abstract : In this work, ionic liquids based on trihexyl(tetradecyl)phosphonium associated with bis(2, 4, 4-trimethylpentyl)phosphinate [TMP] and dicyanamide [DCA] counter anions were used as reactive additives within epoxy/amine networks. Abstract : In this work, ionic liquids based on trihexyl(tetradecyl)phosphonium associated with bis(2, 4, 4-trimethylpentyl)phosphinate [TMP] and dicyanamide [DCA] counter anions were used as reactive additives within epoxy/amine networks. We have demonstrated that the addition of ionic liquids plays a key role on the kinetics of polymerization but also on the final properties of the epoxy networks. Structurations at the nanoscale combined with excellent thermal stability and good mechanical properties have been highlighted. By processing sub-stoichiometric epoxy–amine networks and thanks to the reactivity of phosphinate counter-anions towards glycidyl moieties, more than 70 percent of the ionic liquid was introduced which opens new perspectives in the development of high performance gel electrolytes for the safety improvement of electrochemical devices such as lithium ion batteries.